Implementasi Bahan Ajar Digital dalam Pembelajaran Pendidikan Agama Islam (Studi Kasus di SMPN 1 Kota Sukabumi) - Huzaimah, Siti Haiva; Nugraha, Mulyawan Safwandy (CV. Berkah Cakrawala Inspirasi, 2025)
This study aims to describe the implementation of digital teaching materials in Islamic Religious Education (PAI) learning at SMPN 1 Kota Sukabumi. The background of this research is the need for innovative learning strategies to respond to the development of information technology and to improve students’ learning engagement and understanding. The research focuses on the types of digital teaching materials used, the implementation process in classroom learning, and the challenges faced by teachers and students. This study employed a qualitative research approach with a case study design. Data were collected through classroom observations, in-depth interviews with PAI teachers and students, and documentation analysis. The results show that the implementation of digital teaching materials, such as interactive presentations, learning videos, and digital worksheets, contributes positively to students’ learning motivation and understanding of PAI concepts. Digital materials also support more interactive and student-centered learning activities. However, several obstacles were identified, including limited facilities, varying levels of digital literacy among students, and time constraints in lesson preparation. Overall, the implementation of digital teaching materials is considered effective and has the potential to enhance the quality of PAI learning when supported by adequate infrastructure and teacher competence.